Development Sandwich Wall Panel by Using Recycled Paper for Thermal and Acoustic Properties - Jifferi, Mohd Amri; Mohd Sari, Kamarul Aini; Abdul Rahman, Mohd Fahmi (Progress in Engineering Application and Technology, 2022)
Every month, about 57,000 tonnes of paper are dumped in Malaysian landfills. Thus, this thesis aimed to recycle paper waste combined with resin as a binder to produce a Middle core of Sandwich Wall Panel (SWP), thereby minimizing environmental contamination caused by waste material disposal. The study's objective is to determine an optimum ratio of paper waste and resin and evaluate the materials' physical, acoustic, and thermal conductivity. The study's objective is to determine an optimum ratio of paper waste and resin and evaluate the materials physical, acoustic, and thermal conductivity. According to the result, the density of 30 mm panel paper is 475.93 kg/m3, while that of 15 mm has a density of 437.40 kg/m3. For the impedance tube test, the results show that panel paper is more inclined to high frequency of 0.730 Hz for 30 mm and 15 mm panel paper reaches 0.626 Hz at a distance of 1000 Hz - 5000 Hz. Then, based on the result found 30 mm panel paper has a thermal conductivity of 0.012 Wm/K and a thermal conductivity of 15 mm is 0.011 Wm/K. Comparing to the rice husk, the maximum values are about 0.74 and 0.91 while paper panel the best maximum values sound absorption coefficient is about 0.730 and 0.679 at 1000 Hz to 1000 Hz to 5000 Hz. Due to the difference in thickness between the two materials causing the paper to be less efficient than a rice husk. The proportion was (67%) recycled paper and (33%) resin was used as the binder in SWP manufacturing. Sound absorption and thermal conductivity are affected by thickness density. Density improves efficiency. In other words, panel paper can be used for sound absorption but must be improved to match the rice husk's performance.